Pode a seleção da técnica ser superior ao material escolhido para a união de transferentes? - Mariotto, Guilherme de Aguiar (2018)
STATEMANT OF PROBLEM: The splint transfer technique in implant impression can result in misfit on prosthetic structures. PURPOSE: To evaluate the linear dimensional change of polymerization from 3 materials and 2 techniques of splint transfer technique for implant prostheses used in the open tray technique. MATERIAL AND METHODS: Two implants were installed in a nylon mastermodel whith the shape of a upperjaw, over this two implants, miruscone were tapered. Open tray transfer impression coppings were coupled in to the miruscone, and a silicone guide was made standardizing the unions between the transfers. The samples were divided in six groups (n=20): autopolymerizing acrylic resin Pattern Resin (PA) and Durallay (DU), and bis-acrylic resin Protemp4 (BI), with single step and sectioning and bonding segments techniques (PAC, DUC, BIC). The values of linear dimensional change between these transfers were measured in a profile projector (VB300; Starret) coupled to the Quadra Check apparatus, with a measurement capacity of 0.001 mm, performed by a calibrated single operator. Data were submitted to factorial ANOVA, two-way: Materials and technique (p <0.01) RESULTS: Statistically significant results were found in all comparisons. The PA resin presented the smallest values (μm) of linear dimensional change, both in the single-step technique and in the section and conding, in the following order: BI 255.73(+3.81), DU 173.75(+2.30), PA 95.97(+3.20), BIC 23.82(+1.71), DUC 20.85(+2.53), PAC 13.27(+2.09). The single-step technique obtained worse results regardless of the material. CONCLUSIONS: The sectioning and bonding technique reduced the dimensional change of the samples in all materials, and the Pattern Resin LS presented the lowest contraction, followed by Durallay and Protemp4. CLINICAL IMPLICATIONS: For the transfer splintage in implant prothesis the choice of technique seems to be more importante than the selection of the material to get fidelity of the models